MANAGEMEN PENDIDIKAN PONDOK PESANTREN DALAM PENGEMBANGAN KETRAMPILAN WIRAUSAHA SANTRI - -, Alfan; Mubin, Nurul; Muntaqo, Rifqi (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
This research focuses on the management of Islamic boarding school education implemented by the leadership and administrators of Manbaul Chikmah Kauman Sapuran Wonosobo. It aims to explore how educational management in Islamic boarding schools contributes to the development of students' entrepreneurial skills, including aspects of curriculum design, instructional strategies, and institutional initiatives. A descriptive qualitative approach was employed, utilizing a case study design at Manbaul Chikmah Islamic Boarding School. Data were collected through observations, in-depth interviews, and document analysis. The information was processed through data collection, reduction, presentation, verification, and case analysis. Data credibility was ensured by reference checks, while dependability and confirmability were achieved through supervisory audits. The findings reveal that effective educational management fosters positive institutional change. Improvements occur through structured planning, organizing, directing, and controlling. These management practices are reflected in a responsive curriculum and learning model that align with students' real-world needs. Life skills development—comprising both soft and hard skills—is facilitated through extracurricular programs and entrepreneurship seminars. Activities include public speaking training (khitobah), recitation (tilawah), sewing workshops, and computer networking classes. As a result, students are able to apply these skills in real-world settings within the pesantren environment. Practical implementations include running a student cooperative, managing an Islamic bookstore, participating in a Hajj and Umrah bureau, and operating a tent rental business.